A ética da hospitalidade no acolhimento do outro - Comandulli, Sandra Patricia Eder (My University, 2016)
In this research the aim is to discuss the issue of ethics of hospitality that still defies humanity, in the beginning of XXI century, with disorderly migration and global mobility caused by ethnic-racial and economic conflicts. The text is making a conceptual analysis about the conditional and unconditional hospitality with historical references, based on studies made by Kant, Levinas and Derrida. Kant formalized cosmopolitan rights where the conditions of the universal hospitality are restricted to the rights of access and that only benefit the citizens of the state; Levinas defends the ethics of alterity in which the welcoming is unrestricted and the one hosting has infinite responsibility for the other and that transcends the presence of a third party; and the proposal of Derrida to the concept of hospitality is from the perspective of deconstruction of it, translated into policy and legal opening to move forward on a new responsibility on the subject. In this exercise of understanding the conceptual reach of hospitality, is proposed an analysis of in questioner form and not conclusive about the unconditionality in ethics of Levinas, a contemporary perspective that puts us face to face with paradoxes that permeate the theme of hospitality.
Nesta pesquisa o objetivo é discutir o tema da ética da hospitalidade que ainda desafia a humanidade, nesse início de século XXI, com os fluxos migratórios desordenados e a mobilidade global provocada por conflitos étnico-raciais e econômicos. No texto é feita uma análise conceitual, acerca da hospitalidade condicional e da hospitalidade incondicional com referência histórico-bibliográfica, com base nos estudos feitos por Kant, Levinas e Derrida. Kant formalizou o direito cosmopolita em que as condições da hospitalidade universal estão restritas ao direito de visita e que beneficia somente os cidadãos do Estado; Levinas defende a ética da alteridade em que o acolhimento é irrestrito e o eu que acolhe tem responsabilidade infinita sobre o outro e que transcende a presença de um terceiro; e a proposta de Derrida para o conceito de hospitalidade sob o prisma da desconstrução, traduzida na abertura política e jurídica, para que se avance numa nova responsabilidade quanto ao tema. Neste exercício de compreensão do alcance conceitual de hospitalidade, propõem-se uma análise de forma interrogante e não conclusiva sobre a incondicionalidade na ética de Levinas, numa perspectiva contemporânea que nos coloca frente a paradoxos que perpassam o tema da hospitalidade.
Keywords: Ética; Hospitalidade; Ethics; Hospitality